2003
DOI: 10.1016/s0005-2736(02)00662-4
|View full text |Cite
|
Sign up to set email alerts
|

The general protein secretory pathway: phylogenetic analyses leading to evolutionary conclusions

Abstract: We have identified all homologues in the current databases of the ubiquitous protein constituents of the general secretory (Sec) pathway. These prokaryotic/eukaryotic proteins include (1) SecY/Sec61alpha, (2) SecE/Sec61gamma, (3) SecG/Sec61beta, (4) Ffh/SRP54 and (5) FtsY/SRP receptor subunit-alpha. Phylogenetic and sequence analyses lead to major conclusions concerning (1) the ubiquity of these proteins in living organisms, (2) the topological uniformity of some but not other Sec constituents, (3) the ortholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 61 publications
3
89
1
3
Order By: Relevance
“…33,46 Such an activity is reminiscent of known or postulated roles of polytopic subunits of dedicated protein translocation pathways in bacteria as well as eukaryotic cells. 47,48 Curiously, however, our TrIP studies identified loop P2 and not the TMS or cytoplasmic loops as necessary for the VirB6-substrate close contact. Loop P2 might thus form part of the channel architecture, embedding into the channel either stably or dynamically as a function of substrate transfer.…”
Section: Channel Subunit Versus Substrate Entry Portal?mentioning
confidence: 75%
“…33,46 Such an activity is reminiscent of known or postulated roles of polytopic subunits of dedicated protein translocation pathways in bacteria as well as eukaryotic cells. 47,48 Curiously, however, our TrIP studies identified loop P2 and not the TMS or cytoplasmic loops as necessary for the VirB6-substrate close contact. Loop P2 might thus form part of the channel architecture, embedding into the channel either stably or dynamically as a function of substrate transfer.…”
Section: Channel Subunit Versus Substrate Entry Portal?mentioning
confidence: 75%
“…33 Third, replacement of six residues just preceding TMS4c (Leu164-Met169) by an unrelated polypeptide stretch strongly interferes with protein translocation. 34 The region following TMS4c (Gly182-Pro200) is the most conserved region of the SecY/Sec61α family, 35 that has been proposed to form a hinge region for separation of the two domains of the channel. 12 The data presented here provide clues on how the conformational changes of SecA could result in opening of the SecYEG channel.…”
Section: Discussionmentioning
confidence: 99%
“…The SRP pathway is conserved in all domains of life and has been considered crucial for the vitality of all organisms (2)(3)(4)(5)(6). Saccharomyces cerevisiae represents the only known example of an organism able to endure mutations within the SRP pathway (7).…”
mentioning
confidence: 99%
“…Mutants are exceedingly sick and adapt physiologically by repression of protein synthesis, induction of heat shock genes, and dramatic slow-down of growth (8). Comparative phylogenetic analyses demonstrate that genomes of Eukaryotes, Archaea, and Bacteria encode at a minimum the SRP components SRP54 protein, known in Eubacteria as Ffh (54-kDa homolog), and a 4.5 or 7S small cytoplasmic RNA (scRNA) (5). The third universally conserved element of the pathway is the SRP receptor subunit (SR␣), or in Escherichia coli, FtsY (9).…”
mentioning
confidence: 99%